MEDIA PEMBELAJARAN HURUF KATAKANA BERBASIS DARING DI SMKN 7 PEKANBARU - Theresia Rosari Dj Sinulingga; Rifo Perdana Faizal; Yenny Aristia Nasution (Undiksha Press, 2022)
Based on the results of the explanations that have been presented, it can be concluded that there are differences in learning Katakana letters offline and online at SMKN 7 Pekanbaru. This difference is found in the strategies and learning media used by the teacher. When offline, interactions between teachers and students occur face-to-face. Teachers tend to use discussion strategies and divide students into small groups because they are considered effective for use directly with students. The teacher explains the material directly without having to feel rushed and think about the condition of the network. In online learning, teachers do not use strategies related to performance and small group activities. Teachers are more focused on providing material. When learning offline, the teacher has the flexibility to teach, while when learning online, there is limited time. Time systematic differences were also found between offline learning and online learning. The difference is that offline learning takes longer than online learning. During online learning, the teacher uses PowerPoint Slides which contain learning materials and learning videos. Teachers also use other applications including Google Classroom as a medium for students to collect assignments and ask questions about assignments and Google Meet as a medium for virtual meetings with students. The obstacles that occur in online learning at SMKN 7 Pekanbaru are the instability of the internet network causing the teaching and learning process to be disrupted, teachers' difficulty monitoring students, the difficulty of finding a conducive learning environment for students and there are some students who do not have devices for online learning.